Spawn : Godslayer - Holguin, Brian (Holguin, Brian. Spawn., 2025)
"A dramatic reimagining of Todd McFarlane's Spawn. This epic tale of fallen kingdoms, ancient curses, and tragic love will captivate fans of fantasy and adventure. In a distant age, in a world not our own, the Old Gods are dying, slaughtered one by one by the dark blade of a mysterious, unearthly marauder. Under the protection of the goddess Llyra, the island kingdom of Endra-La, the oldest and most storied of the Shrouded Isles, has avoided the cruel fate that has befallen lesser kingdoms. But on the eve of a royal wedding, black sails appear on the horizon. Alarms are sounded, and fire fills the skies. The Godslayer has come for them at last."